(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of intracranial bleed in infants with vitamin-K deficiency in 7-180 days of age. Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at the Department of Pediatrics STH, Swat from 1st July 2016 to 30th June 2017. Materials and Methods: Biodata, clinical profile and results of the investigations (coagulation profile and neuroimaging) of all theselected patients were collected on a pre designed proforma. Total of 100 patients were included who fulfilled the inclusion criteria of the study. Exclusion criteria were strictly observed to prevent confounder and bias. Results: Out of 100 patients 65(65%) were male and 35(35%) were female. Intracranial bleed due to Vitamin-K deficiency was confirmed in 31(31%) patients. The mean age of onset of symptoms was 45.65 ± 15.35 days and male to female ratio 1.85:1 (p=0.047). 16 (51.61%) out of 31 patients with intracranial bleed were from 7-60 days of life, 10(32.25%) were from 61-120 days of life and only 5(16.12%) beyond 120 days of life. Conclusion: Intracranial hemorrhage remains a disabling disease mostly due to unidentifiable causes, however in many cases a high index of suspicion of Vitamin K deficiency should be kept in mind which often leads to bleeding as identified in our study.